2023
DOI: 10.1186/s12882-023-03075-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low-dose rituximab as induction therapy for antineutrophil cytoplasmic antibody-associated vasculitis with renal involvement: a Chinese case series

Abstract: Background Rituximab (RTX) is a standard therapy for antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). However, the most frequently used dose may lead to severe adverse effects (SAEs). We explored the efficacy and safety of low-dose RTX in Chinese patients with AAV. Methods A total of 22 Chinese patients diagnosed with AAV with renal involvement, including 8 treated with low-dose RTX (400 mg of RTX total over 4 weeks) and 14 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study also found that a higher baseline CD19 + B-cell count and the use of trimethoprim-sulfamethoxazole for prevention could reduce the risk of severe infections such as Pneumocystis jirovecii. A study ( Liu et al, 2023 ) focusing on Chinese patients with AAV found that low-dose RTX therapy (total dose of 400 mg within 4 weeks) was comparable in efficacy to CYC therapy but significantly reduced the incidence of serious adverse events (SAEs). Similarly, a real-world study ( Ishikawa et al, 2024 ) in Japan suggested that RTX may have a lower risk of fungal infections and Pneumocystis pneumonia compared to CYC in critically ill patients with AAV.…”
Section: Biologicsmentioning
confidence: 99%
“…The study also found that a higher baseline CD19 + B-cell count and the use of trimethoprim-sulfamethoxazole for prevention could reduce the risk of severe infections such as Pneumocystis jirovecii. A study ( Liu et al, 2023 ) focusing on Chinese patients with AAV found that low-dose RTX therapy (total dose of 400 mg within 4 weeks) was comparable in efficacy to CYC therapy but significantly reduced the incidence of serious adverse events (SAEs). Similarly, a real-world study ( Ishikawa et al, 2024 ) in Japan suggested that RTX may have a lower risk of fungal infections and Pneumocystis pneumonia compared to CYC in critically ill patients with AAV.…”
Section: Biologicsmentioning
confidence: 99%